Effectiveness of international environment law - Zayd Elmal, Safia (Journal of Human Sciences, 2021)
The growing interest in environmental protection has been instrumental in pushing countries to conclude many international environmental conventions, and enacting new principles for emission of pollution issues. Environmental conventions are the most common means of establishing binding international environmental norms. Where the areas are covered, however, the environment remains under constant and growing threat. The rules formulated in many conventions are general, flexible and sometimes uncoordinated and do not contain sufficient deterrent penalties to enforce compliance, so they are ineffective and relative in providing environmental protection, and compliance with environmental conventions is based on interests and material possibilities, The nature of international law was based primarily on the principle of sovereignty. No international body could impose on another State the obligation to abide by any convention